Jump and balance test in judo athletes with or without visual impairments - Spera, R.; Belviso, I.; Sirico, F.; Palermi, S.; Massa, B.; Mazzeo, F.; Montesano, P. (Journal of Human Sport & Exercise, 2019)
The study was conducted for four months with 8 judo athletes: 4 sighted people (4 M) and 4 visual impairment people (3 M and 1 F), aged between 18 and 52 (30.75 ± 12.74). According to the IBSA Visual Classification, all visual impairment subjects participating in our study were covered in the B1 category of visual deficit. This is a group represented by patients with no light perception in either eye up to light perception, and with an inability to recognize the shape of a hand at any distance or in any direction. From our cohort it was excluded subjects who have had low extremities musculoskeletal, neurological, or orthopaedic disorders in the previous six months. The aim of the study was to evaluate their balance with both closed and opened eyes and to set their lower limbs` strength: these are indispensable characteristics to carry out technical actions of judo. Anthropometric measures were compared between groups and data about jump protocol and balance protocol were analysed. Results of current research showed that postural stability is different in function of assessment with closed and open eyes. The result of the jump tests differs because the data do not show significant differences between long jump and high jump. The comparison between blinded and sighted judo athletes highlighted greater difficulties with eyes closed for sighted athletes than blinded ones.